The Influence Of Graphic Organizers, Language Aptitude And Attitude Towardsstudents'english Learning Achievement - Threesje Roza Souisa (Department of English Language Education, UIN Sunan Ampel Surabaya, 2020)
As one of the tools that can be applied in teaching and learning process, a graphic organizer is the most effective strategy that recommended by researchers not only in improving students’ English necessary skills but also in reducing students’ negative attitude on learning English. This study was conducted to find out the positive and significant influence of graphic organizer as the delivery strategy towards the students’ reading ability as well as to figure out the positive and meaningful interaction between graphic organizers, language aptitude and students’ attitude towards students’ English learning achievement. Quasi-experiment with a nonequivalent control group design was applied by involving 160 students as the subject of the study. The results showed that there was a positive and significant effect among Graphic Organizers and language aptitude as the main effect, and there were significant interaction effects among them in improving students’ reading ability.